The Hidden Genomic and Transcriptomic Plasticity of Giant Marker Chromosomes in Cancer. Issue 3 (1st March 2018) - Macchia, Gemma; Severgnini, Marco; Purgato, Stefania; Tolomeo, Doron; Casciaro, Hilen; Cifola, Ingrid; L'Abbate, Alberto; Loverro, Anna; Palumbo, Orazio; Carella, Massimo; Bianchini, Laurence; Perini, Giovanni; et al.
Abstract: Neocentromeres contribute to cancer progression by mitotically stabilizing acentric chromosomes containing amplified oncogenes. Macchia et al . show that... Genome amplification in the form of rings or giant rod-shaped marker chromosomes (RGMs) is a common genetic alteration in soft tissue tumors. The mitotic stability of these structures is often rescued by perfectly functioning analphoid neocentromeres, which therefore significantly contribute to cancer progression. Here, we disentangled the genomic architecture of many neocentromeres stabilizing marker chromosomes in well-differentiated liposarcoma and lung sarcomatoid carcinoma samples. In cells carrying heavily rearranged RGMs, these structures were assembled as patchworks of multiple short amplified sequences, disclosing an extremely high level of complexity and definitely ruling out the existence of regions prone to neocentromere seeding. Moreover, by studying two well-differentiated liposarcoma samples derived from the onset and the recurrence of the same tumor, we documented an expansion of the neocentromeric domain that occurred during tumor progression, which reflects a strong selective pressure acting toward the improvement of the neocentromeric functionality in cancer. In lung sarcomatoid carcinoma cells we documented, extensive "centromere sliding" phenomena giving rise to multiple, closely mapping neocentromeric epialleles on separate coexisting markers occur, likely due to the instability of neocentromeres arising in cancer cells. Finally, by investigating the transcriptional activity of neocentromeres, we came across a burst of chimeric transcripts, both by extremely complex genomic rearrangements, and cis / trans -splicing events. Post-transcriptional editing events have been reported to expand and variegate the genetic repertoire of higher eukaryotes, so they might have a determining role in cancer. The increased incidence of fusion transcripts, might act as a driving force for the genomic amplification process, together with the increased transcription of oncogenes.